2016
DOI: 10.1039/c6ra08873b
|View full text |Cite
|
Sign up to set email alerts
|

A quantum chemical approach towards understanding stability and tautomerism of 2-imino-2H-pyran derivatives

Abstract: The ring-chain tautomerism of 2-imino-2H-pyran derivatives annelated with an aromatic or aliphatic ring and their transformation into corresponding 2-pyridons were studied based on the relative stabilities of two series of model isomers calculated by the DFT method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The use of piperidine as catalyst in i-PrOH under microwave irradiation at 100 ºC during 5 min [8] resulted in formation of pure expected product 8a, but the isolated yield was again very low (12%, Entry 9). Further experiments with catalytic amounts of piperidine, its stoichiometric quantities and excess at higher temperatures (Entries [10][11][12][13][14] showed that under such conditions increasing amounts of the undesired by-product 10a appeared in the isolated material. The reaction carried out at 160 °С during 20 min under microwave irradiation gave the pure by-product (10a, Entry 15).…”
Section: Search For Optimal Reaction Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of piperidine as catalyst in i-PrOH under microwave irradiation at 100 ºC during 5 min [8] resulted in formation of pure expected product 8a, but the isolated yield was again very low (12%, Entry 9). Further experiments with catalytic amounts of piperidine, its stoichiometric quantities and excess at higher temperatures (Entries [10][11][12][13][14] showed that under such conditions increasing amounts of the undesired by-product 10a appeared in the isolated material. The reaction carried out at 160 °С during 20 min under microwave irradiation gave the pure by-product (10a, Entry 15).…”
Section: Search For Optimal Reaction Conditionsmentioning
confidence: 99%
“…Selected representatives were analyzed by means of IR spectroscopy, mass-spectrometry, LC-MS and elemental analysis, 13 C NMR, APT NMR as well as HSQC and HMBC correlation NMR spectroscopy. NMR spectra were recorded on a Bruker Avance drx 500MHz (126MHz for 13 C NMR; Bruker Spectrospin Ltd., Coventry, United Kingdom), Varian MR 400MHz spectrometer (100MHz for 13 C NMR), and Varian Mercury VX 200MHz (Varian Inc., Palo Alto, CA) using DMSO-d 6 as a solvent and residual solvent signal as the reference (TMS scale). IR spectra were recorded on a Perkin Elmer Spectrum One FTIR spectrometer (PerkinElmer, Inc., Shelton, CT) (in KBr pellets).…”
Section: General Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some commercially available coumarin-based drugs are shown in Figure 1 [17][18][19][20]. Among coumarin derivatives, enamines derived from coumarins are proven to be important compounds that can act as anti-tumor, antibacterial, antiproliferative, and antifungal agents [21,22]. Different strategies can be used to derivatize these heterocyclic compounds, but multistep synthesis routes often affect the yields of the final products.…”
Section: Introductionmentioning
confidence: 99%